Chitosan thymol nanoparticles improve the antimicrobial effect and the water vapour barrier of chitosan-quinoa protein films. (January 2019) - Medina, Estefanía; Caro, Nelson; Abugoch, Lilian; Gamboa, Alexander; Díaz-Dosque, Mario; Tapia, Cristian
Abstract: The aim of this work was to improve the performance of quinoa protein/chitosan edible films on the extension of postharvest life of blueberries and tomato cherries by addition of chitosan thymol nanoparticles prepared by ionic gelation. These nanoparticles were effective at inhibiting the mycelial growth of Botrytis cinerea. Films with nanoparticles were significantly more effective in reducing water vapour permeability than were films with sunflower oil and film control without nanoparticles. Films with nanoparticles were applied as an internal coating to a polyethylene terephthalate (PET) clamshell container to store blueberries and tomato cherries, and the weight loss was evaluated. The weight loss for both foods stored in modified PET clamshells was significantly lower than that in the unmodified PET clamshell during storage at 7 °C and 85% RH for 10 days. Thus, chitosan thymol nanoparticles have a potential application as an antimicrobial for preservation of fresh fruits and as a water vapour barrier when these particles are added into chitosan-quinoa protein films. Highlights: Chitosan thymol nanoparticles (CTNPs) inhibit the mycelia growth of Botrytis cinerea . The water vapour barrier of chitosan-quinoa protein film is enhanced with CTNPs. Films with CTNPs were used as internal coating of clamshells containing fruits. These clamshells modified are effective to reduce the weight loss.